Impact of Pulmonary Embolism Response Team on Anticoagulation Prescribing Patterns in Patients With Acute Pulmonary Embolism. (February 2022) - Kuhrau, Shannon; Masic, Dalila; Mancl, Erin; Brailovsky, Yevgeniy; Porcaro, Katerina; Morris, Stephen; Haines, Jeremiah; Charo, Kim; Fareed, Jawed; Darki, Amir
Introduction: Anticoagulation remains the mainstay pharmacotherapy for acute pulmonary embolism (PE), but multiple treatment options exist. The Pulmonary Embolism Response Team (PERT) is a multidisciplinary group that evaluates patients, formulates evidence-based treatment plans, and mobilizes resources. The objective of this study was to characterize the anticoagulation prescribing patterns made by PERT and to determine the clinical impact of anticoagulant selection. Materials and Methods: This was a retrospective analysis of patients evaluated by PERT from 2016 to 2018. Multivariable linear regression was conducted to determine predictors of length of stay (LOS). Results: A total of 209 patients were evaluated by PERT and received anticoagulation on discharge. Of those, 47% received a non-vitamin K oral anticoagulant (NOAC), 29% received warfarin, and 23% received low-molecular-weight heparin. Patient preferences and comorbidities were the most common reasons for NOAC omission. Patients who received NOACs had a shorter median LOS than warfarin (6.1 [4.6-7.6] days vs 10.9 [8.4-13.4] days; P < .05). Selection of NOAC upon discharge was the only factor independently associated with reduced LOS (β coefficient: −0.6; 95% CI: −1.01 to −0.18; P < .01). Conclusion: The most common recommendation made by PERT was to initiate a NOAC upon discharge, resulting in shorter hospital LOS compared to patients who received warfarin.